An audit of corneal abrasion management following the introduction of local guidelines in an accident and emergency department. Issue 7 (22nd June 2006) - Thyagarajan, S K; Sharma, V; Austin, S; Lasoye, T; Hunter, P
Abstract : Background and objectives: Corneal abrasions are a common presentation to accident and emergency (A&E) departments. Patients can be treated and discharged by A&E staff without the need for an ophthalmologist's attention; complicated cases, however, should be recognised and referred. Inexperience and limited training in ophthalmology may lead to suboptimal patient care and inappropriate use of ophthalmology outpatient clinics. Issues of poor documentation may also arise. The purpose of this audit was to assess the effect of guidelines on the management of corneal abrasion by A&E staff. Methods: A retrospective case note audit was performed to assess current management of corneal abrasions. Guidelines for management of corneal abrasions were formulated following a literature search and collaboration between A&E and ophthalmology staff. A prospective case note audit was undertaken to assess management after introduction of the guidelines. Results: A total of 51 cases were audited before the introduction of the guidelines and 57 cases after. Following the introduction of the guidelines documentation of visual acuity increased to 93% and specific enquiry into contact lens wear rose from 35.3% to 71.9%. A&E staff stopped giving out local anaesthetic eye drops. The follow up profile also improved; appropriate patient discharges increased by 40% whereas inappropriate referrals to eye clinic dropped by 75%. More patients were given abrasion advice (a 101% increase). Conclusions: A&E staff members are capable of managing corneal abrasions if they are given guidance and some training. This audit identified shortcomings in current management and showed that guidelines can significantly improve clinical practice.